2020
DOI: 10.1021/acs.langmuir.0c00034
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of a Metal–Polymer Interface Observed by Element-Specific Focused Ion Beam-Scanning Electron Microscopy

Abstract: The degradation of a metal−polymer interface was studied in three dimensions using focused ion beam-scanning electron microscopy (FIB-SEM) with energy-dispersive X-ray spectroscopy. A brass-rubber interface, which is important for tires, was examined as an example of a metal-polymer interface. Brass-plated steel cords were embedded in rubber, which was then vulcanized. The brass-rubber interface was treated at 70 °C under 96% humidity for up to 14 days (a wet-heat aging treatment). FIB-SEM provided clear three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…In summary, it revealed that the Cr-coated steel and EAA were tightly bonded by the chromium oxide layer. Since different valences of elements have an effect on the adhesion between metals and polymers, 13,50,51 further TEM analysis was performed for better understanding of the interfacial phases of the laminated steel-EAA strip. Figure 7a shows the BF image of the interface at a lower magnification than Figure 6a for the purpose of observing a larger crosssectional view, which displays the grain size on the metal side.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In summary, it revealed that the Cr-coated steel and EAA were tightly bonded by the chromium oxide layer. Since different valences of elements have an effect on the adhesion between metals and polymers, 13,50,51 further TEM analysis was performed for better understanding of the interfacial phases of the laminated steel-EAA strip. Figure 7a shows the BF image of the interface at a lower magnification than Figure 6a for the purpose of observing a larger crosssectional view, which displays the grain size on the metal side.…”
Section: Resultsmentioning
confidence: 99%
“…Scanning electron microscopy (SEM) is applied to observe the morphology, , while transmission electron microscopy (TEM) not only has higher resolution for observation, but can also be used for phase identification . Furthermore, electron microscopy equipped with energy-dispersive X-ray spectroscopy (EDX) can be used to analyze the chemical composition at the interface. Another technique used for identifying interfacial phases is X-ray diffraction (XRD). Tan et al found that a new phase formed at the interface of a carbon fiber-reinforced polyether ether ketone and titanium alloy system prepared by laser joining, which was identified as CTi 0.42 V 1.58 by XRD characterization on the cross section.…”
Section: Introductionmentioning
confidence: 99%
“…In the tire industry, steel cords within the tire need to be brass-plated on their surface to enhance the tire durability because the rubber would peel off from the steel cord without brass coating and cause the tire to burst. , Besides, the valve of the inner tube of the tire also mainly consists of brass, to strengthen the binding at the rubber–metal boundary. Pioneering studies have reported that the high strength of rubber binding to brass is derived from the formation of a nonstoichiometric copper sulfide (Cu x S) intermediate layer at the rubber–metal contact boundary upon vulcanization. , Nonstoichiometric Cu x S grows as dendrites into the viscous rubber during the initial stage. When the Cu x S growth levels off, the cross-linking of the viscoelastic rubber entrapped in the dendrites would result in tight interlocking of the rubber in the Cu x S dendrites .…”
Section: Introductionmentioning
confidence: 99%
“…When the Cu x S growth levels off, the cross-linking of the viscoelastic rubber entrapped in the dendrites would result in tight interlocking of the rubber in the Cu x S dendrites . The tight and physical interlocking forces between the Cu x S layer and the vulcanized rubber are the main factor for the high binding strength. , The chemical cross-linking via Cu–S–rubber is also proposed, but its contribution toward the rubber–brass adhesion is considered minor. ,, In the battery industry, copper (Cu) foils and organic polymers are used as current collectors and binders, respectively. Therefore, the concept of the binding mechanism at the rubber–metal boundary can be extensively applied in lithium-ion batteries to strength the binding force between sulfur-containing polymer binders and Cu current collectors.…”
Section: Introductionmentioning
confidence: 99%
“…From several microscopic and spectroscopic studies such as scanning electron microscopy (SEM), cross-sectional transmission electron microscopy (TEM), X-ray photoelectron spectroscopy (XPS) depth profiling, Raman spectroscopy, time-of-flight secondary ion mass spectrometry (TOF-SIMS), and X-ray diffraction (XRD), it has been inferred that various factors such as interface thickness, morphology, crystal phase, and chemical composition at the interface play a significant role in enhancing adhesion between brass and rubber. However, these techniques have their own limitations and inadequacies. ,,,,,,, Some limitations include a cumbersome preparation process (sectioning and ion polishing) for TEM and damage of the sample due to the use of argon ion (Ar + ) sputtering (for XPS), and therefore a new methodology for the measurement of interfacial characteristics is necessary. , …”
Section: Introductionmentioning
confidence: 99%